1977
DOI: 10.1073/pnas.74.11.5131
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of murine Ia alloantigens determined by the i-E/i-C subregions of the H-2 complex.

Abstract: Alloantisera directed against the alloantigens determined b the I-E and IC subregions of the murine major histocompatibility complex precipitate two components that have molecular weights of 35,000 and 29,000. These components, when analyzed by partial NH2-terminal sequencing, show no homology to two components of similar size determined by the I-A subregion. However, the large chain determined by the murine I-E and/or IC subregion is homologous to the large chain of the human HILA-D region alloantigen, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Both react with B lymphoid cells (15,22,23) and are potent inhibitors of mixed lymphocyte reactions (10,11,15,24). Also, incubation of target cells with F(ab)2 fragments of xenoantisera (12,25) (6,7,26) as well as shifts in molecular weights of presumedly HLA-D locus gene products p29 and p34 have been observed previously (20). The …”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…Both react with B lymphoid cells (15,22,23) and are potent inhibitors of mixed lymphocyte reactions (10,11,15,24). Also, incubation of target cells with F(ab)2 fragments of xenoantisera (12,25) (6,7,26) as well as shifts in molecular weights of presumedly HLA-D locus gene products p29 and p34 have been observed previously (20). The …”
Section: Methodsmentioning
confidence: 76%
“…The methods used for the isolation, purification, and sequence analysis of Ia alloantigens from murine spleen cells are identical to those previously published (6). The serological properties of the alloantisera (B10 X HTI)F1 anti-B1O.A (5R) and (A.TH X B1O.HTT)F1 anti-A.TL, used to isolate I-C subregion and I-A subregion molecules from B10.D2 and B10.A (4R) mice, respectively, have also been described (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…trols the cell surface expression of an Ia molecule whose polymorphic determinants are largely controlled by the I-A subregion. Cook, Vitetta, Uhr, and Capra (81) and later Silver et al (82) confirmed these findings and demonstrated that the I-E subregion controls the synthesis of the Ia Ea chain which on the cell surface is noncovalently associated with the p chain determined in the I-A subregion (Figs. 2 and 6).…”
Section: Function Of Ir Genesmentioning
confidence: 78%
“…Cook, Vitetta, Uhr and Capra (81) and later Silver et al (82) confirmed these findings and demonstrated that the 1-E subregion controls the synthesis of the Ia Ea chain which on the cell surface is noncovalently associated with the β chain determined in the I-A subregion (Figs. 2 and 6).…”
Section: The La Molecules Are the Ir Gene Productsmentioning
confidence: 77%